Impact of Lobbying on Competition in the Banking Sector - Fu, Jingbo (Université d'Ottawa | University of Ottawa, 2013)
This paper considers the impact of lobbying activities on the degree of competition in the banking sector. It is an empirical study using the conceptual framework of the “General Equilibrium Lobbying Game with a Banking Sector” by Perez-Saiz & Semenov (2013). We test the hypothesis that stronger lobbying activities result in higher competition level and lower profit margin in the industry. We conduct a panel-data regression by analyzing the profit margin in the U.S. at the state level after financial crisis. There are significant negative impacts from dollar amount and number of lobbying contributions. The result is consistent with the hypothesis. It predicts a non-linear effect of lobbying efforts, as well as the “Local Persistent Effect”. There are two extensions: an examination of the lobbying lag effect and an analysis of the before-financial-crisis sample.